Diploma of Whiteness : Race and Social Policy in Brazil, 1917-1945 - Dávila, Jerry, 1970- (Book collections on Project MUSE., 2003)
Asserts that Brazilian mid-century educational reforms, designed to end rigid, race-based exclusions and to incorporate the poor, did so by stressing whiteness as the primary characteristic of modernity.